The Effect of Perception of Organizational Support, Work Motivation and Competence on Employee Performance at the Tirta Moedal Drinking Air Company in Semarang City - Shafai Dewa Mirza; Herry Subagyo (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
Employee performance is a key factor in supporting organizational success, particularly in public service companies like Perumda Air Minum Tirta Moedal Semarang City. Various factors can influence performance, including perceived organizational support, work motivation, and individual competence. This study aims to analyze the influence of perceived organizational support, work motivation, and competence on employee performance. This study used a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees of Perumda Air Minum Tirta Moedal Semarang City. The data analysis technique used was multiple linear regression to determine the effect of each independent variable on the dependent variable. The results of this study are expected to demonstrate that perceived organizational support, work motivation, and competence have a significant and positive influence on employee performance. These findings are expected to provide a basis for management in formulating human resource development policies to improve the effectiveness and efficiency of company services. This research also provides theoretical contributions to the field of human resource management and practical implications for employee performance management in regional companies.